Häresis — ein Wort[,] das wieder zu Ehren gebracht werden sollte: Schleiermacher als Ökumeniker - Jüngel, Eberhard (Zeitschrift für Theologie und Kirche, 1999)
The article takes up a phrase from Schleiermacher's Reden über die Religion, an expression which allows the reader to see the various historical religions as individual realizations of the one, whole religion in a positive sense as heresies which are united in one (invisible) church. This insight is of lasting significance. In an ecumenical respect — in accordance with guidelines of the 'Glaubenslehre' — it is to be used for the benefit of the relationship among the Christian denominations. However the expression 'heresy' then regains its 'heretical' meaning.